Sweet taste exposure and the subsequent acceptance and preference for sweet taste in the diet: systematic review of the published literature. Issue 3 (16th March 2018) - Appleton, KM; Tuorila, H; Bertenshaw, EJ; de Graaf, C; Mela, DJ
ABSTRACT: Background: There are consistent, evidence-based global public health recommendations to reduce intakes of free sugars. However, the corresponding evidence for recommending reduced exposure to sweetness is less clear. Objective: Our aim was to identify and review the published evidence investigating the impact of dietary exposure to sweet-tasting foods or beverages on the subsequent generalized acceptance, preference, or choice of sweet foods and beverages in the diet. Design: Systematic searches were conducted to identify all studies testing relations of variation in exposure to sweetness through foods and beverages with subsequent variation in the generalized acceptance, preference, or choice of sweetened foods or beverages, in humans aged >6 mo. Results: Twenty-one studies met our inclusion criteria, comprising 7 population cohort studies involving 2320 children and 14 controlled trials involving 1113 individuals. These studies were heterogeneous in study design, population, exposure, and outcomes measured, and few were explicitly designed to address our research question. The findings from these were inconsistent. We found equivocal evidence from population cohort studies. The evidence from controlled studies suggests that a higher sweet taste exposure tends to lead to reduced preferences for sweetness in the shorter term, but very limited effects were found in the longer term. Conclusions: A small and heterogeneous body of research currently has considered the impact of varying exposure to sweet taste on subsequent generalized sweet taste preferences, and this evidence is equivocal regarding the presence and possible direction of a relation. Future work should focus on adequately powered studies with well-characterized exposures of sufficient duration. This review was registered with PROSPERO as CRD42016051840, 24 November 2016.